Molecular species identification for multiple carnivores - Cisneros Vidal, R. (2017)
Species identification is crucial for carnivore conservation and ecological studies. We present a simple molecular genetic test that amplifies DNA of 16 wild carnivore species from three continents. The test is based on co-amplification of two mitochondrial DNA fragments and scoring of the resulting species-specific size patterns. We evaluated the performance of this method using 332 known tissue, blood, hair and fecal samples from 23 carnivore and 11 potential prey species. Results demonstrate that this test can distinguish many Caniform species but not members of Felidae. The test can be performed with a single PCR and capillary sequencer run for cost-effective processing of large sample numbers typical of non-invasive genetic projects.